Replication-dependent unhooking of DNA interstrand cross-links by the NEIL3 glycosylase - Semlow, Daniel R. (Cell, 2016)
During eukaryotic DNA interstrand cross-link (ICL) repair, cross-links are resolved (“unhooked”) by nucleolytic incisions surrounding the lesion. In vertebrates, ICL repair is triggered when replication forks collide with the lesion, leading to FANCI-FANCD2-dependent unhooking and formation of a double-strand break (DSB) intermediate. Using Xenopus egg extracts, we describe here a replication-coupled ICL repair pathway that does not require incisions or FANCI-FANCD2. Instead, the ICL is unhooked when one of the two N-glycosyl bonds forming the cross-link is cleaved by the DNA glycosylase NEIL3. Cleavage by NEIL3 is the primary unhooking mechanism for psoralen- and abasic site-ICLs. When N-glycosyl bond cleavage is prevented, unhooking occurs via FANCI-FANCD2-dependent incisions. In summary, we identify an incision-independent unhooking mechanism that avoids DSB formation and represents the preferred pathway of ICL repair in a vertebrate cell-free system.